Analisis Faktor-Faktor yang Mempengaruhi Minat Siswa Melanjutkan Studi ke Perguruan Tinggi - Muhtar, Novia Rizki; Chamidi, Agus Salim (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
This study aims to (1) determine the effect of motivation on interest in continuing studies at university at MAN 2 Kebumen; (2) determine the effect of student willingness on interest in continuing studies at university at MAN 2 Kebumen; (3) determine the effect of family environment on interest in continuing studies at university at MAN 2 Kebumen; and (4) determine the effect of school environment on interest in continuing studies at university at MAN 2 Kebumen. This study used a quantitative approach. The population in the study were all grade XII students of MAN 2 Kebumen, while the sample used was 80 respondents. The research instrument was a questionnaire with a Likert scale. Data analysis was carried out using validity tests, reliability tests, classical assumption tests, multiple linear regression tests, hypothesis testing through t-tests and f-tests, and coefficient of determination (R2) analysis using SPSS. The results showed that the motivation variable had a significant effect on student interest with a calculated t-value of 6.955 > 1.665. The student willingness variable had a significant effect with a calculated t-value of 3.250 > 1.665. The family environment variable has a significant effect with a calculated t value of 2.348 > 1.665. While the school environment variable has a significant effect with a calculated t value of 2.736 > 1.665. Based on the determination coefficient value of 0.93, which means that 93% of student interest is influenced by the variables of motivation, student willingness, family environment, and school environment, while the remaining 7% is influenced by other variables outside the study.